整体煤气化联合循环合成气水合物法分离CO2的分子动力学模拟 - 颜克凤; 李小森; 陈朝阳; 徐纯钢 (2010)
Molecular dynamics (MD) simulation is used to study the microscopic mechanism of CO2 separation from integrated gasification combined cycle (IGCC) syngas (CO2/H-2) via the hydrate formation The stable structures and microscopic properties of CO2 hydrate, H-2 hydrate, and CO2/H-2 hydrate from one stage separation for IGCC syngas are investigated systematically. The binding energy for loading the hydrate structure with the guest molecules, Delta E-n was analyzed It was shown that the binding between CO2 and water is more stable than that between H-2 and water That is, CO2 can more easily form the hydrate Therefore. CO2 in the CO2/H-2 gas mixture more easily transfers into the hydrate phase. Based on this, CO2 can be separated from the IGCC syngas. The binding energy for loading the single cavity with the guest molecules, Delta E-GH, was analyzed It was found that the gas mixture can form structure I (SI) hydrate, in which CO2 molecules preferably occupy the big cavity and then occupy the small cavity, and H-2 molecules only occupy the small cavity. The simulation was carried out at pressure of 8.5 MPa and temperature of 273.7 K for the stable structure of the CO2/H-2, hydrate in one stage separation for IGCC syngas From the Delta E-n and Delta E-GH of the systems with H-2 single and double occupancy in the small cavity, it is concluded that the configurations with the single occupancy is most stable. The stable structure of the hydrate in one stage separation is attained by MD. It provides a theoretical evidence Of CO2 separation for formation hydrate in IGCC syngas. 利用分子动力学（MD）模拟方法研究整体煤气化联合循环（IGCC）合成气（CO2/H2）水合物法分离CO2的分离机理,系统研究了CO2水合物、H2水合物以及合成气水合物法一级分离所得CO2/H2混合气体水合物的微观结构及性质.模拟分析n个CO2或H2与水合物笼状结构的整体结合能ΔEn,得出CO2比H2与笼状结构结合更稳定,易形成水合物.因此,CO2/H2混合气体中CO2更易进入水合物中,从而达到IGCC合成气中CO2分离效果.模拟分析气体水合物（GH）中CO2,H2与单胞腔的结合能ΔEGH,得出采用合成气水合物法分离CO2形成结构Ⅰ型（SⅠ）水合物,CO2首先占据大胞腔,其次占据小胞腔,H2只能占据小胞腔.同时模拟温度为273.7K和压力为8.5MPa条件下一级分离所得CO2/H2混合气体水合物构象,分析H2单占据和双占据SⅠ水合物小胞腔的ΔEn和ΔEGH,结果表明H2单占据稳定.通过MD模拟得出一级分离稳定水合物构象,为IGCC合成气水合物法分离CO2提供了理论指导.